High Voltage Stability and Characterization of P2‐Na0.66Mn1‐yMgyO2 Cathode for Sodium‐Ion Batteries. Issue 15 (30th June 2020) - Or, Tyler; Kaliyappan, Karthikeyan; Bai, Zhengyu; Chen, Zhongwei
Abstract: The development of sodium‐ion batteries is currently limited by the availability of high‐energy and low‐cost cathode materials. The energy density of cathodes can be maximized by expanding the voltage range for cycling, but this often leads to severe capacity degradation. Cathodes that demonstrate good long‐term cyclability at high voltage cut‐offs (>4.3 V vs Na/Na + ) are scarce in the literature. In this work, layered P2‐Na0.66 Mn1‐ y Mg y O2 was synthesized by using a modified Pechini method at various compositions ( y =0, 0.05, 0.1) and characterized after extended cycling between 2–4.5, 4.6, and 4.7 V vs. Na/Na + . Na0.66 Mn0.95 Mg0.05 O2 displayed a similar initial discharge capacity to Na0.66 MnO2 with significant improvements in cycle retention. It was most promising when cycled between 2 and 4.5 V, retaining 140 mAh g −1 (82 % retention) and 116 mAh g −1 (68 % retention) after 50 and 100 cycles, respectively, at low current (40 mA g −1 ). A higher Mg dopant quantity led to improvements in cyclability and rate performance albeit with lower initial discharge capacity. Electrochemical and physical (ex situ XRD) characterizations were used to delineate the role of high‐voltage phase transitions, SEI layer formation, electrolyte solvent insertion into sodium slabs, and active material degradation/dissolution toward capacity loss. Abstract : Character witness : The performance and behavior of P2‐Na0.66 Mn1‐ y Mg y O2 is systematically tested and characterized at various Mg doping compositions and upper cut‐off voltages. The failure mechanisms typically observed at high voltage cycling are assessed. The material demonstrates promise as a high capacity and environmentally benign cathode for sodium‐ion batteries.